Power loss analysis of a multiport DC – DC converter for DC grid applications - Samende, C; Mugwisi, N; Rogers, DJ; Chatzinikolaou, E; Gao, F; McCulloch, M (IEEE, 2018)
In this paper, power losses of a multiport DC - DC converter are analysed. The converter has four bidirectional ports and consists of a triple active bridge and four half bridge converters. As a result, sixteen different operating modes, defined by all combinations of power flow direction, are possible. The converter power losses and resulting efficiencies vary widely with operating conditions. This paper presents methods to accurately calculate the efficiency of the four-port converter in each operating mode using component datasheet information, taking into account losses in the transformer of the triple active bridge converter, passive components and semiconductors. A 200 W converter prototype is used to experimentally validate the loss model for one specific operating mode.